Dendritic design as an archetype for growth patterns in nature: fractal and constructal views - Miguel, Antonio F. (Frontiers in Physics, 2014)
The occurrence of configuration (design, shape, structure, rhythm) is a universal phenomenon that occurs in every flow system. Dendritic configuration (or tree-shaped configurations) is ubiquitous in nature and likely to arise in both animate and inanimate flow systems. Why is it so important? Is there a principle from which this configuration can be deduced? In this review paper we show that these systems own two of the most important properties of fractals that are self-similarity and scaling. Their configuration do not develop by chance. It´s occurrence is a universal phenomenon of physics covered by a principle. Here we also show that the emergence of dendritic configuration in flow systems constitutes a basic supportive flow path along which “order” need to persist is propagated.